Komunikasi Organisasi Kesatuan TNI Korem 023/ Kawal Samudera Dalam Penanganan Bencana Banjir Longsor 2025 di Kota Sibolga - Anggi Nihma Aulia; Sigit Hardiyanto (Universitas Muhammadiyah Sumatera Utara, 2026)
This study aims to analyze organizational communication in flood and landslide disaster management in Sibolga City in 2025. The study used a qualitative descriptive method with data collection techniques through interviews, observation, and documentation. The results show that organizational communication is structured, hierarchical, and two-way through a command system. Communication patterns include vertical and horizontal communication, both formal and informal, between agencies. The communication strategy focuses on the speed and integration of information through the main command post and the use of communication technology. The communication channels used are diverse, thus supporting smooth coordination in emergency situations. Communication also plays a crucial role in increasing the effectiveness of disaster management by accelerating decision-making and cooperation between agencies.